Fantasy football and managerial economics. (19th January 2010) - Logan, Jennifer; Sutter, Daniel
The National Football League (NFL) is USA's most popular team sport, and educators have found 'fantasy football' to be a valuable teaching vehicle. This paper discusses several exercises using fantasy football to facilitate students' understanding of principles of managerial economics and the use of business statistics in the decision-making process. The assignments are suitable for courses in managerial economics and business statistics. The exercises provide students with an intuitive application of basic business statistics and to acquire an understanding of the theoretical framework in which statistics is taught.